A Morphokinematic Study of the Enigmatic Emission Nebula NGC 6164/5 Surrounding the Magnetic O-type Star HD 148937 - Beomdu Lim; Yaël Nazé; Seok-Jun Chang; Damien Hutsemékers (The Astrophysical Journal, 2024)
HD 148937 is a peculiar massive star (Of?p) with a strong magnetic field (1 kG). The hourglass-shaped emission nebula NGC 6164/5 surrounds this star. This nebula is presumed to originate from episodic mass-loss events of the central O-type star, but the detailed formation mechanism is not yet well understood. Grasping its three-dimensional structure is essential to uncovering the origin of this nebula. Here we report the high-resolution multiobject spectroscopic observations of NGC 6164/5 using the GIRAFFE on the 8.2 m Very Large Telescope. Integrated intensity maps constructed from several spectral lines delineate well the overall shape of this nebula, such as the two bright lobes and the inner gas region. The position–velocity diagrams show that the two bright lobes are found to be redshifted and blueshifted, respectively, while the inner region has multiple layers. We consider a geometric model composed of a bilateral outflow harboring nitrogen-enriched knots and expanding inner shells. Its spectral features are then simulated by using a Monte Carlo radiative transfer technique for different sets of velocities. Some position–velocity diagrams from simulations are very similar to the observed ones. According to the model that best reproduces the observational data, the two bright lobes and the nitrogen-enriched knots are moving away from HD 148937 at about 120 km s ^−1 . Their minimum kinematic age is estimated to be about 7500 yr. We discuss possible formation mechanisms of this nebula in the context of binary interaction.